The Influence of Social Media on the Eating Patterns of Students at the Faculty of Public Health, Universitas Sumatera Utara in 2023 - Namora Lumongga Lubis; Estomihi Simanjuntak; Melania Stevani (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Social media refers to platforms and applications that utilize internet-based technology. This type of media promotes and facilitates connections with others. Social media has an important role in the eating patterns of students at the Faculty of Public Health at the Universitas Sumatera Utara. If social media use is wrong, it will impact the quality of students' eating patterns, resulting in a wrong body mass index. This research aims to investigate how social media factors affect eating habits. The study will employ an explanatory survey method with a cross-sectional approach. This research was carried out in September 2023. The population in this research were all students of the Faculty of Public Health at the Universitas Sumatera Utara, with a total of 390 people and a sample of 80 people. The samples taken in this study were students at the Faculty of Public Health, Universitas Sumatera Utara, using the Slovin technique. Slovin's formula is a statistical method used to determine an appropriate sample size when conducting surveys or research. It helps to ensure that the sample accurately represents the population while minimizing the cost and effort involved in data collection. Data was collected using a questionnaire. Based on the research results, it was found that 46 respondents (57.5%) had a poor eating pattern, and 34 respondents (42.5%) had a good eating pattern. Based on the Bivariate test, the variable related to eating patterns is the influence of social media (p=0.002). From the data processing results, it is concluded that social media significantly influences eating patterns.Universitas Sumatera Utara. I hope the university and faculty can provide additional education regarding social media and healthy eating patterns to students at the Universitas Sumatera Utara. Universitas Sumatera Utara. Keywords: Social Media, Eating Patterns, Student